Honours and (re)design of the curriculum: How to bridge the gap between honours and bachelor programmes - Annelies Riteco; Irene de Kleyn; Nicolle Lamerichs (Journal of the European Honors Council, 2017)
Since 2016 the University of Applied Sciences Utrecht (Hogeschool Utrecht, HU) has been implementing a new HU Honours vision with value creation as the core element. Honours students realize value creation on several levels: personal growth and professional identity, and they deliver products or services that add value to professional practice and wider society. HU Honours education, which is accessible for all ambitious and talented students, offers five types of honours tracks. In order to bridge the gap between honours education and the bachelor programmes, new honours tracks are designed at the same time the regular courses are (re)designed. Honours is structurally embedded in the educational innovations and vice versa: honours is an excellent stimulus for curriculum (re)design because there are more innovative opportunities to set up learning and teaching in different ways. This integration of curriculum renewal and honours programme development has given a boost to new honours tracks and to talent development of all ambitious and talented students.